Poppy Harmon and the pillow talk killer - Hollis, Lee (Hollis, Lee. Desert Flowers mysteries, 2022)
"Cast in her first role since the 1980s, Poppy has never been more rattled or unprepared on a film set. It's an embarrassing but necessary cover to keep an eye on client Danika Delgado, a rising starlet and social media influencer with a large following -- including a dangerous stalker who won't disappear. The leading lady's fame is growing, and so are the threats against her life ... Unfortunately for Poppy, there's more to fear than flubbed lines. When she finds Danika smothered to death in her trailer at Joshua Tree National Park, the horrifying crime stirs up memories of a man known as the Pillow Talk Killer during her time as a young actress, bringing unsolved murders from the past back into focus ... A trail of clues urges Poppy, hunky sidekick Matt Flowers, and the rest of the Desert Flowers Detective Agency gang on a frantic chase after Danika's crazed #1 fan. But as co-stars and production crew members start looking equally suspicious, Poppy must expose a slew of insidious industry secrets before a murderer rolls out the red carpet for someone else ..." --